SIFAT PAPAN WOL KAYU DARI 20 JENIS KAYU KALIMANTAN TIMUR - Rozak Memed; Paribotro Sutigno; M Isa Iskandar (Pusat Penelitian dan Pengembangan Hasil Hutan, 1984)
The results of laboratory test on the properties of wood-wool boards manufactured from 20 individual wood species obtained from East Kalimantan province are reported in this paper. The tests comprised board density, moisture content thickness reduction due to compression and bending strength.The results reveal an average yield of wood-wool of 419 kg per cubic meter of log input, and CaCl2 mineralizing fluid produced better quality boards compared with those using Ca (OH)2.